2019
DOI: 10.1111/mcn.12754
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of breast milk substitute feeding among newborns in delivery facilities in urban Cambodia and Nepal

Abstract: Introducing breast milk substitutes (BMS) in the first days after birth can increase infant morbidity and reduce duration and exclusivity of breastfeeding. This study assessed determinants of BMS feeding among newborns in delivery facilities in Phnom Penh, Cambodia, and Kathmandu Valley, Nepal. Cross‐sectional surveys were conducted among mothers upon discharge from health facilities after delivery: 304 mothers in Kathmandu Valley and 306 mothers in Phnom Penh participated. On the basis of a conceptual framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 63 publications
4
18
0
Order By: Relevance
“…In particular, it has limited measures to protect against engagement with health workers and promotion of BMS to the general public. In our study, mothers feeding BMS were more likely to have a health worker recommend BMS compared with breastfeeding mothers, a trend witnessed in other LMIC (Champeny et al, 2019;Rothstein et al, 2020). Exposure to commercial BMS promotions was nearly universal in our study, and recent research documented rampant promotion of BMS in retail locations throughout Bandung City (Hadihardjono et al, 2019).…”
Section: Maternal Educationsupporting
confidence: 60%
“…In particular, it has limited measures to protect against engagement with health workers and promotion of BMS to the general public. In our study, mothers feeding BMS were more likely to have a health worker recommend BMS compared with breastfeeding mothers, a trend witnessed in other LMIC (Champeny et al, 2019;Rothstein et al, 2020). Exposure to commercial BMS promotions was nearly universal in our study, and recent research documented rampant promotion of BMS in retail locations throughout Bandung City (Hadihardjono et al, 2019).…”
Section: Maternal Educationsupporting
confidence: 60%
“…Timely initiation of breast-feeding has a positive impact to decrease PLF practices (15,42,43) . Our results showed that the risk of PLF increased gradually as the initiation time of breast-feeding increased.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have to raise awareness about the poor breastfeeding practices among the population from suburban area of Phnom Penh, where only one third reached the criteria for appropriate breastfeeding practice for children under 6 months of age. The increase in the use of commercial baby foods and infant formula might be one of the drivers for the poor achievement of breastfeeding practices [36].…”
Section: Discussionmentioning
confidence: 99%